Neutrino decay and neutrinoless double beta decay in a 3-3-1 model - Dias, A. G.; Doff, A.; Pires, CAD; da Silva, PSR (American Physical Soc, 2005)
In this work we show that the implementation of spontaneous breaking of the lepton number in the 3-3-1 model with right-handed neutrinos gives rise to fast neutrino decay with Majoron emission and generates a bunch of new contributions to the neutrinoless double beta decay.